SIRMIUM BISHOPS 1229–1534 - Борис Стојковски (Истраживања, 2012)
On the basis of the archive materials of primarily Hungarian and other diplomats, and numerous literature, the paper attempts to create hitherto the most complete and the most accurate chronological order of Roman Catholic Sirmium bishops in the Sirmium bishopric from its foundation in 1229 to the Battle of Mohacs in 1526, and to the fall of the medieval Hungarian kingdom. Unfortunately, there are few data on the majority of the bishops, and enough information only about some of the bishops. The author tried to reconstruct as many bishops’ biographies as possible, as well as the details of their bishop post in Sirmium in the Middle Ages. For most of them, there were just data witnessing when the numerous charters of Hungarian kings were brought on various issues. The biography of all the bishops before their arrival to Sirmium, and after their departure, was reconstructed wherever it was possible. A special attention was paid to the famous church dignitaries who left an indelible mark in the history of medieval Hungary, and humanists who were at the head of the Sirmium Diocese.